The Role of Forensic Biology in Realising MaqÄsid al-Shariah (The Objectives of Islamic Law) (Sains Humanika, 2015)
MaqÄsid al-Shariâ€™ah preserves every masÄlih or al-DaruriyyÄt (essential), followed by the al-HajiyyÄt (complementary benefits) and the al-TahsiniyyÄt (embellishments) hierarchically. The most famous al-DaruriyyÄt discussed in usÅ«l al-fiqh (Islamic Jurisprudence) by Islamic scholars are Hifz al-Din (the preservation of religion/faith), Hifz al-Nafs (the preservation of life), Hifz al-â€˜Aql (the preservation of intellect), Hifz al-Nasl/nasb (the preservation of life age) and Hifz al-MÄl (the preservation of property). Hence, it is absolutely necessary to preserve these values for the sake of maintaining tranquillity and calmness. Consequently, forensic biology has been proven consistently has its own role in order to preserve the al-DaruriyyÄt al-Khamsah. Contributing towards tranquillity and calmness through the priority of justice for example, forensic biology has shown its function years by years with the advanced development and rapid evolution of technology, has helped a lot in convicting crimes. This indicates that forensics itself is an important part in bringing the element of justice in Hifz al-Nafs. As an illustration, DNA typing, fingerprint analysis, odontology, serology and others play important role towards realising maqÄsid al-Shariâ€™ah. Yet, researches have to be conducted to correlate on all these items mentioned. As a pioneer, this article aims to demonstrate on how forensic biology could realise maqÄsid al-Shariâ€™ah. The objectives are to highlight the relations between al-Bayyinah and maqÄsid al-Shariâ€™ah, to highlight the relations of al-Qarinah and forensic biology, to analyse on cases that solve by forensic biology which under the theme of al-DaruriyyÄt al-Khamsah. As a significant, research uses content analysis on selected cases of study and document analysis by literature review as the methodology. At the end, research found that forensic biology can be classified under the topic of al-Qarinah in al-Bayyinah, al-Bayyinah is one of prior means to achieve maqÄsid al-Shariâ€™ah in Islamic criminal law, DNA profiling, fingerprint analysis and serology play vital role in realising maqÄsid al-Shariâ€™ah and forensic biology helps in realising maqÄsid al-Shariâ€™ah through the preservation of al-DaruriyyÄt al-Khamsah.Â
Keywords: Forensic biology; DNA profiling; fingerprint analysis; serology; maqasid al-Shari'ah; al-Qarinah